Hyaluronic acid—Based wound dressings: A review - Graça, Mariana F.P.; Miguel, Sónia P.; Cabral, Cátia S.D.; Correia, Ilídio J. (Carbohydrate polymers, 2020)
[Display omitted] •HA is a biocompatible and biodegradable ECM compound that encourage the wound healing.•HA-based wound dressings present excellent performance in treatment of wounds.•The synthesis of HA-derivatives augments its stability and mechanical properties.•The biomolecules loading into HA wound dressings improves the biological activity. Hyaluronic acid (HA), a non-sulfated glycosaminoglycan (GAG), is a major component of skin extracellular matrix (ECM) and it is involved in the inflammatory response, angiogenesis, and tissue regeneration process. Due to the intrinsic properties of HA (such as biocompatibility, biodegradability and hydrophilic character), it has been used to produce different wound dressings, namely sponges, films, hydrogels, and electrospun membranes. Herein, an overview of the different HA-based wound dressings that have been produced so far is provided as well as the future directions regarding the strategies aimed to improve the mechanical stability of HA-based wound dressings, along with the incorporation of biomolecules intended to ameliorate their biological performance during the healing process.